Sekulerisasi Yoga dalam Pariwisata Bali - I Gede Sutarya (UHN IGB Sugriwa Denpasar, 2018)
Yoga is a search for tourists in Bali tourism which is spread in some destinations in Bali such as in Ubud, Seminyak and Sanur. This search for yoga is a form of health search that is different from the purpose of yoga to achieve moksha (eternal happiness). This gap raises research questions about the form of yoga secularization in Bali tourism. This article reviews the form of yoga secularization in Balinese tourism according to the theory of historical materialism which states that the basic principle of change is matter. This article is based on qualitative research carried out in series in 2016 and 2017. The result is that the form of yoga secularization in Balinese tourism occurs through changes in orientation to health, changes in yoga techniques to healing techniques, exchange with money, and the use of science-technology. Changes are forms of secularization in yoga.